2022
DOI: 10.1159/000524290
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Stroke and Vaccine-Induced Immune Thrombotic Thrombocytopenia following COVID-19 Vaccine: A Case Report with Systematic Review of the Literature

Abstract: <b><i>Introduction:</i></b> Vaccine-induced immune thrombotic thrombocytopenia (VITT) is a prothrombotic syndrome observed after adenoviral vector-based vaccines for severe acute respiratory syndrome coronavirus 2. It is characterized by thrombocytopenia, systemic activation of coagulation, extensive venous thrombosis, and anti-platelet factor 4 antibodies. Arterial thrombosis is less common and mainly affects the aorta, peripheral arteries, heart, and brain. Several cases of ischemic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Seven cases of AIS with LVO who have thrombocytopenia underwent mechanical thrombectomy successfully and safely among our studied patients, 6 of them did not receive IV tPA prior to thrombectomy [ 29 , 108 , [110] , [111] , [112] ]. Cascio Rizzo et al also indicated that despite that re-occlusion after revascularization may happen due to the hypercoagulative state, mechanical thrombectomy is a feasible and safe treatment in patients with VITT and AIS [ 113 ]. It is suggested not to use intravenous heparin throughout the thrombectomy procedure in these patients [ 108 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seven cases of AIS with LVO who have thrombocytopenia underwent mechanical thrombectomy successfully and safely among our studied patients, 6 of them did not receive IV tPA prior to thrombectomy [ 29 , 108 , [110] , [111] , [112] ]. Cascio Rizzo et al also indicated that despite that re-occlusion after revascularization may happen due to the hypercoagulative state, mechanical thrombectomy is a feasible and safe treatment in patients with VITT and AIS [ 113 ]. It is suggested not to use intravenous heparin throughout the thrombectomy procedure in these patients [ 108 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thrombosis combined with thrombocytopenia after vaccination has been termed vaccine-induced prothrombotic immune thrombocytopenia (VIPIT), VITT, or thrombosis with thrombocytopenia syndrome (TTS). VITT has been mostly reported after immunization with adenovirus vector-based vaccines against COVID-19 [ 13 , 14 , 15 , 16 , 17 ]. The mean age of patients with VITT was 45.6 years (95% CI 43.8–47.4, I2 = 57%), with a female predominance (70%) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of patients with VITT was 45.6 years (95% CI 43.8–47.4, I2 = 57%), with a female predominance (70%) [ 15 ]. Another systemic review presented a median age of 45.5 years [ 17 ]. One systemic review included 27 patients with the occurrence or relapse of thrombotic thrombocytopenic purpura (TTP) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, negative or obscure results for ELISA have been used in several cases. 42 43 In Scully et al's publication in June 2021, an individual with elevated D-dimer, low fibrinogen, and deep venous thrombosis and bilateral adrenal hemorrhage had an ambiguous ELISA level of 0.156 optical density on the Asserachrom HPIA IgG assay. 20 Likewise, a clinically indistinguishable individual tested negative on ELISA (Lifecodes PF4 IgG assay) and functional HIT assay.…”
Section: Diagnostic Criteria and Guidelinesmentioning
confidence: 99%